The Development of Chinese Sculpture in the 1980s–2020s in Chinese Art Studies - Song, Yanbo (HUDPROM: The Ukrainian Art and Design Journal, 2024)
The development of sculpture remains a subject of sustained interest in Chinese art studies. This attention is driven by several key directions that collectively define the role and position of contemporary sculpture within the broader trajectory of Chinese fine arts. One such direction is the exploration of the concept of “modernity,” which, in the context of sculptural practice, exhibits distinctive chronological markers, internal content, and modes of expression. The analysis of sculpture as an independent genre of fine art also holds significant relevance. This line of inquiry is characterized by universal features, is grounded in a wide stylistic paradigm, and reveals a clear evolutionary dynamic. Such an approach enables scholars to identify and trace the main stages in the formation of stylistic identities in sculpture and provides a foundation for integrating the history of sculpture into the overall history of Chinese fine arts. Accordingly, the study of Chinese sculpture from the 1980s to the early 2020s emerges as a pressing historiographical issue in Chinese art scholarship. The article demonstrates that within this field, the development of sculpture is examined through lenses that highlight the emergence of a new artistic language. Researchers place particular emphasis on the concept of “modernity” in sculpture, which reflects the adoption of novel artistic approaches that emerged in the 1990s and 2000s. The classification of sculptural works as “modern” pertains to their conceptual framework, a notion most comprehensively articulated by Deng Pingxiang (邓平祥). He proposed an analytical model for modern sculpture that includes new formalism in plasticity, innovative material aesthetics, and the novelty of the artist’s figurative perspective. Equally important in scholarly discourse is the universalist approach, through which scholars examine the overall landscape of Chinese sculpture from the 1990s to the 2020s. For many, this framework offers a means to construct the most comprehensive and integrated vision of the field. Prominent representatives of this approach include leading scholars He Guiyang (何桂彦) and Sun Zhenhua (孙振华).